Auditorio 400 at the 'Museo Reina Sofia' in Madrid: Use of variable systems for acoustic improvements. Issue 3 (September 2016) - Ortiz, Silvia M
This article will describe the different acoustic problems identified in Auditorio 400 and possible solutions to these acoustic deficiencies using variable acoustic systems such as movable panels with different absorption coefficients and reflectors suspended from the ceiling. Due to the various types of events that take place in this hall, the Auditorio 400 must have proper acoustics for speech as well as music presentations and concerts, and this implies different configurations of sound sources. The auditorium has an innovative style and the solution presented in this article maintains this architectonic and aesthetic style while still improving the acoustics of the venue.